The Role of Self-Doubt in Character Development of Stephanie in Andrew Knauer’s Senior Year 2022 - Putriana, Kadek Olivia Novi; Kartiningsih, Rindrah; H, Hariyono (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research aims to develop a model of Christian Religious Education that is oriented towards improving This article examines the role of self-doubt in character development through a detailed analysis of Stephanie Conway, the main character of Senior Year 2022, written by Andrew Knauer. Using Creswell’s qualitative research method, this article analyzes how Stephanie’s journey of self-doubt shapes her emotional and psychological growth. The story is about the character’s journey from her teenage years that focuses on becoming popular and getting into an accident that put her in a coma for 20 years. The analysis delves into the ways in which self-doubt influences her decisions and interactions, through in-depth narrative analysis and character examination, this paper highlights how self-doubt is integral to the development of Stephanie’s character, illustrating its role in her eventual path to self-acceptance.